Pseudopotential theory for the explanation of energetics of self-diffusion by a vacancy mechanism - Ghorai, Amitava (Diffusion Fundamentals, 2023)
Harrison’s pseudopotential approach of the derivation of activation energy for self-diffusion in metallic solids is explained here from the energy difference between pure lattice and otherwise activated lattice in relaxed conditions. This difference depends on the structure factor of the lattice and modifications in the lattice wave numbers. Separate expressions for monovacancy formation energy and monovacancy migration energy with relaxation energy of surrounding nearest neighbours are also calculated.